2002
DOI: 10.1128/aem.68.6.2934-2942.2002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Flow Cytometric Method To Analyze Subpopulations of Bacteria in Probiotic Products and Dairy Starters

Abstract: Flow cytometry (FCM) is a rapid and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 38 publications
5
93
0
1
Order By: Relevance
“…[3,23] In vitro survival studies recommended 10 9 -10 10 CFU daily dose for probiotic effects since 10 6 CFU/ml might be insufficient as not all bacteria reach the intestines alive. [24] The present study identified a range of 2.2-3.0 × 10 10 CFU per 80-ml bottle of Philippine Yakult monitored for a period of 31 days, which is comparable with the identified approximately 3.0 × 10 10 CFU per 65-ml recommended dose bottle of Yakult [25] containing at least 1.0 × 10 8 CFU/ml at the expiry date. [11] Plate counting has been employed in most researches for the assessment of probiotic viability.…”
Section: Discussionsupporting
confidence: 55%
“…[3,23] In vitro survival studies recommended 10 9 -10 10 CFU daily dose for probiotic effects since 10 6 CFU/ml might be insufficient as not all bacteria reach the intestines alive. [24] The present study identified a range of 2.2-3.0 × 10 10 CFU per 80-ml bottle of Philippine Yakult monitored for a period of 31 days, which is comparable with the identified approximately 3.0 × 10 10 CFU per 65-ml recommended dose bottle of Yakult [25] containing at least 1.0 × 10 8 CFU/ml at the expiry date. [11] Plate counting has been employed in most researches for the assessment of probiotic viability.…”
Section: Discussionsupporting
confidence: 55%
“…This technique has demonstrated its potential as a means to assess the physiological state of damaged cells (Ueckert et al 1997). FCM has been successfully used in several studies to assess the viability of microbial cells in probiotic products and dairy starters (Bunthof and Abee 2002), starved cultures Kaprelyants et al 1996), cells having been exposed to antibiotics (Novo et al 2000) or high hydrostatic pressure (Ritz et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such DNA-intercalating dyes are able to bind upon exposure to bright visible light to DNA and, consequently, to inhibit PCR amplification of the DNA which is free or inside the bacterial cells with the damaged membrane. Although probiotic bacteria in the products are represented in different stages not only as viable or dead (Bunthof and Abee, 2002), the most important criterion for distinguishing between viable and irreversibly damaged cells is membrane integrity. The treatment of bacteria with EMA as a promising tool of DNA-based differentiation between viable and dead pathogenic bacteria was first proposed by Nogva et al in 2003(Nogva et al, 2003.…”
Section: Viability Determination Of Probiotics By Pcr-based Methodsmentioning
confidence: 99%